Do hospital type or caseload make a difference in chemotherapy treatment patterns for early breast cancer?: results from 104 German institutions, 2008-2017 - Riedel, Fabian; Hoffmann, Ann Sophie; Moderow, Mareike; Feißt, Manuel; Heublein, Sabine; Deutsch, Thomas M.; Schäfgen, Benedikt; Golatta, Michael; Domschke, Christoph; Wallwiener, Markus; Heil, Jörg; Hennigs, André (The breast, 2021)
Background - Over the past decade, chemotherapy has been used more selectively in early breast cancer (EBC) due to better risk stratification. Neoadjuvant chemotherapy (NACT) has evolved to the primary treatment option. The type and size of hospitals is known to have a substantial influence on the kinds of treatment they provide, and therefore on patient outcomes (e.g. rates for pathological complete response, pCR), but it is not yet known how this has affected delivery of chemotherapy for EBC in Germany. - Methods - This study analyzed chemotherapy use and pCR rates after NACT for EBC patients treated at 104 German institutions 2008-2017. Institutions were separated into associated hospital type (university hospital; teaching hospital; community hospital) and annual caseload (≤100; 101-250; >250 cases/year). - Results - Overall, 124,084 patients were included, of whom 11.6% were treated at university hospitals, 63.1% at teaching hospitals, and 25.3% at community hospitals. In total, 46,274 (37.3%) received chemotherapy, of whom 44,765 had information available about systemic treatment and surgery. From 2008 to 2017, chemotherapy use declined from 48.3% to 36.4% for university hospitals, from 40.7% to 30.3% for teaching hospitals, and from 42.4% to 33.7% for community hospitals. Furthermore, the proportion of NACT increased the most in university hospitals (from 32.0% to 68.1%); whereas, the rate of pCR (defined as ypT0 ypN0) increased irrespective of institutional type. Analyses regarding annual caseload did not show any differences. - Conclusions - The results from this large, nationwide cohort reflect a more selective use of chemotherapy in Germany, irrespective of institutional type or case load.
Gesehen am 14.07.2021